The intercultural communication research theories in the globalization context (Journal of Philosophy Culture and Political Science, 2016)
Modern globalization, on the one hand, brings peoples and cultures in a common cultural space, but on the other – it is associated with the process of cultural identity erosion. Therefore, the dialogue and intercultural communication issues become relevant in the modern world and in the Kazakh society.
Keywords: intercultural communication; globalization; culture; communicant; identity.